If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6z + -1) + -4(z + 3) = 3(z + 1) Reorder the terms: 3(-1 + 6z) + -4(z + 3) = 3(z + 1) (-1 * 3 + 6z * 3) + -4(z + 3) = 3(z + 1) (-3 + 18z) + -4(z + 3) = 3(z + 1) Reorder the terms: -3 + 18z + -4(3 + z) = 3(z + 1) -3 + 18z + (3 * -4 + z * -4) = 3(z + 1) -3 + 18z + (-12 + -4z) = 3(z + 1) Reorder the terms: -3 + -12 + 18z + -4z = 3(z + 1) Combine like terms: -3 + -12 = -15 -15 + 18z + -4z = 3(z + 1) Combine like terms: 18z + -4z = 14z -15 + 14z = 3(z + 1) Reorder the terms: -15 + 14z = 3(1 + z) -15 + 14z = (1 * 3 + z * 3) -15 + 14z = (3 + 3z) Solving -15 + 14z = 3 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -15 + 14z + -3z = 3 + 3z + -3z Combine like terms: 14z + -3z = 11z -15 + 11z = 3 + 3z + -3z Combine like terms: 3z + -3z = 0 -15 + 11z = 3 + 0 -15 + 11z = 3 Add '15' to each side of the equation. -15 + 15 + 11z = 3 + 15 Combine like terms: -15 + 15 = 0 0 + 11z = 3 + 15 11z = 3 + 15 Combine like terms: 3 + 15 = 18 11z = 18 Divide each side by '11'. z = 1.636363636 Simplifying z = 1.636363636
| 0(-19)= | | 3x+2=-5 | | 3(x+4)-6x=2(4-2x) | | -5y+12=67 | | -4(w-9)(-w+1)=0 | | -3y+9=-4y+6 | | x^2+13=8x | | -3x+7-2x=4x-6+8 | | (5z-9)(7+z)=0 | | 40+4y-12=12y-14-2y | | -3(2s-1)-3=-2(s+8)-2 | | 5u(u-8)(u-3)=0 | | Z-3*10=10 | | I-19I= | | 6y+13=55 | | X+4+3=17 | | 25x-10-16X=3(3X-4)+2 | | 3y-5+y+33=8y+30-6y | | Y=0.493x-973.4 | | 58=11x+3 | | 13x+72=-7x-28 | | 11-3x+5=10 | | 6.4x+2.3x=-65.6 | | 5(x+5)+3=18 | | 17x+4=-21-8x | | 4(2x+1)-3x=14 | | 12x^4y^3-20x^2y=0 | | a^3-125= | | 8w+3=5w+7+4w | | 6.4x-2.3x=65.6 | | 8-3(5-x)=14 | | 6x+11x=85 |